Cyborgs in Latin America - Brown, J. Andrew (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org . Cyborgs in Latin America explores the ways cultural expression in Latin America has grappled with the changing relationships between technology and human identity.